A REALITY OF MAN - Edmundas Krakauskas (Problemos)
Almost four hundred years ago R. Descartes (1596–1650) argued cogito ergo sum. This argument has been analyzed up to the present day and will continue to be analyzed in the future. Is man real as a spiritual being or is he with two natures: material and spiritual? A man is not material (that is his body). The words man and body are not synonyms. Man is only real as a rational being; he is only an understandable phenomenon. The body is a phenomenon of sensation (that is, at the biological level). The argument for the material nature of man is impossible; in such a case the argument itself must be treated as a natural phenomenon.